Uranium speciation in groundwaters from Parana basin, Brazil - Bonotto, Daniel Marcos [UNESP] (A A Balkema Publishers, 1999)
This paper describes the results of a regional study involving the sampling of 60 pumped tubular wells drilled at the Parana sedimentary basin, Brazil, which was carried out with the purpose of evaluating the U speciation in the Botucatu-Piramboia aquifer. Uranium proved to be intensively dissolved even under the enhanced reducing conditions occurring at the most confined zones of the aquifer, and Eh-pH diagrams were utilized to evaluate the influence of temperature and pressure on the migration of the U-species within the aquifer.